Endovascular therapy in acute anterior circulation large vessel occlusive patients with a large infarct core (ANGEL-ASPECT): protocol of a multicentre randomised trial - Liping Liu; Yongjun Wang; Yilong Wang; Zhongrong Miao; David S Liebeskind; Vitor Mendes Pereira; Zeguang Ren; Xiaochuan Huo; Yuesong Pan; Xuelei Zhang; Gaoting Ma; Xu Tong; et al. (Stroke and Vascular Neurology)
Background The benefit of stroke thrombectomy for large infarct core still lacks robust randomised controlled studies.Aim To demonstrate the design of a clinical trial on endovascular therapy for acute anterior circulation large vessel occlusion (LVO) patients with large infarct core volume.Design ANGEL-ASPECT is a multicentre, prospective, randomised, open-label, blinded End-point trial to evaluate whether best medical management (BMM) combined with endovascular therapy improves neurological functional outcomes as compared with BMM alone in acute LVO patients with Alberta Stroke Program Early CT Score (ASPECTS) of 3–5 on non-contrast CT or infarct core volume range of 70–100 mL (defined as rCBF <30% on CT perfusion or ADC <620 on MRI) up to 24 hours from symptom onset or last seen well.Study outcomes The primary efficacy outcome is 90 (±7) days modified Rankin Scale. Symptomatic intracranial haemorrhage within 48 hours from randomisation is the primary safety outcome.Discussion The ANGEL-ASPECT trial will screen patients with large infarct core (ASPECTS 3–5 or 70–100 mL) through image evaluation criteria within 24 hours and explore the efficacy and safety of endovascular therapy compared with BMM.